Computational paradigm for Mg-Li alloy innovation: Decoding atomic doping mechanisms for targeted property enhancement - Wei Cheng; Ben Jia; Zhicheng Dong; Zhengying Wu; Xin Zhao; Xiaopeng Wan; Zhuo Liu; Heyuan Huang (Results in Engineering, 2025)
Magnesium (Mg) - Lithium (Li) alloys are the world's lightest alloys and thus have great application potential in the field of lightweight materials. Alloy element doping is a key strategy to enhance the thermomechanical properties of Mg-Li alloys, and first-principles calculations based on density functional theory (DFT) have become an important means to explore the doping strengthening mechanism. However, most existing studies adopt a top-down analysis approach, and the explanation of the strengthening mechanism of doped atoms is still shallow, failing to fully leverage the economic and efficiency advantages of computer-aided technology. This work systematically sorts out the core role of DFT in explaining the strengthening mechanism of metals, and through the construction of theoretical models and simulation calculations, reveals the electronic structure and chemical bond change rules at the atomic scale; it focuses on reviewing how DFT has helped to analyze the influence mechanisms of different doped elements on the crystal structure, mechanical properties, and corrosion resistance of Mg-Li alloys during their development process; and it discusses the application of DFT in the functional design of Mg-Li alloys. The research points out that the current application of DFT has limitations such as insufficient multi-scale coupling analysis and lagging experimental verification. Therefore, it is proposed to combine molecular dynamics simulation and high-throughput computing to provide theoretical support for the precise design and industrial application of doping strengthening of Mg-Li alloys, which has important scientific significance and practical value for promoting the development of the lightweight materials field.